Machinery of the Government Part II-B Madhya Pradesh - Government of Madhya Pradesh, Administrative Reforms Commission (Government of Madhya Pradesh, Administrative Reforms Commission, 1972)
The prime purpose of the Ministry of Industrial Development is to generate, nourish and sustain the industrial growth of the State. The State carries a crushing burden of unemployment, under-employment and disguished unemployment as its economy is, in the main, agricultural. The potential for industrial development is accepted to be immense. But what is needed is much greater information, energy and the will to take the necessary steps al the right time, expeditiously and with a view to getting things done.